Association of phthalates, parabens and phenols found in personal care products with pubertal timing in girls and boys. Issue 1 (4th December 2018) - Harley, Kim G; Berger, Kimberly P; Kogut, Katherine; Parra, Kimberly; Lustig, Robert H; Greenspan, Louise C; Calafat, Antonia M; Ye, Xiaoyun; Eskenazi, Brenda
Abstract: STUDY QUESTION: Are in-utero or peripubertal exposures to phthalates, parabens and other phenols found in personal care products associated with timing of pubertal onset in boys and girls? SUMMARY ANSWER: We found some associations of altered pubertal timing in girls, but little evidence in boys. WHAT IS KNOWN ALREADY: Certain chemicals in personal care and consumer products, including low molecular weight phthalates, parabens and phenols, or their precursors, are associated with altered pubertal timing in animal studies. STUDY DESIGN, SIZE, DURATION: Data were from the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) longitudinal cohort study which followed 338 children in the Salinas Valley, California, from before birth to adolescence. PARTICIPANTS/MATERIALS, SETTING, METHODS: Pregnant women were enrolled in 1999–2000. Mothers were mostly Latina, living below the federal poverty threshold and without a high school diploma. We measured concentrations of three phthalate metabolites (monoethyl phthalate [MEP], mono- n -butyl phthalate and mono-isobutyl phthalate), methyl and propyl paraben and four other phenols (triclosan, benzophenone-3 and 2, 4- and 2, 5-dichlorophenol) in urine collected from mothers during pregnancy and from children at age 9. Pubertal timing was assessed among 179 girls and 159 boys every 9 months between ages 9 and 13 using clinical Tanner staging. Accelerated failure time models were used to obtain mean shifts of pubertal timing associated with concentrations of prenatal and peripubertal biomarkers. MAIN RESULTS AND THE ROLE OF CHANCE: In girls, we observed earlier onset of pubic hair development with prenatal urinary MEP concentrations and earlier menarche with prenatal triclosan and 2, 4-dichlorophenol concentrations. Regarding peripubertal biomarkers, we observed: earlier breast development, pubic hair development and menarche with methyl paraben; earlier menarche with propyl paraben; and later pubic hair development with 2, 5-dichlorophenol. In boys, we observed no associations with prenatal urinary biomarker concentrations and only one association with peripubertal concentrations: earlier genital development with propyl paraben. LIMITATIONS, REASONS FOR CAUTION: These chemicals are quickly metabolized and one to two urinary measurements per developmental point may not accurately reflect usual exposure. Associations of peripubertal measurements with parabens may reflect reverse causality: children going through puberty early may be more likely to use personal care products. The study population was limited to Latino children of low socioeconomic status living in a farmworker community and may not be widely generalizable. WIDER IMPLICATIONS OF THE FINDINGS: This study contributes to a growing literature that suggests that exposure to certain endocrine disrupting chemicals may impact timing of puberty in children. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the National Institute of Environmental Health Sciences and the US Environmental Protection Agency. The authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.